Modernisasi Hukum Indonesia melalui Revisi KUHPerdata - Abunawas Abunawas; Amriani Amir; El Hendrianto (Mahesa Research Center, 2023)
The article on the modernization of Indonesian law through revision of the Undang-undang Hukum Perdata (KUH Perdata) aims to analyze the relevance of the Civil Code to current conditions and identify articles in the Civil Code that are no longer relevant to current developments. The research was carried out using a qualitative descriptive method, focusing on a problem based on facts obtained through observations, interviews and studying documents or references that are relevant to the topic being written. This research was carried out by collecting data from various sources such as literature, legal documents and previous research results that are relevant to the data needed. Furthermore, the data obtained was then analyzed qualitatively by identifying patterns and themes that emerged from the data. This research also uses a textual and contextual approach in analyzing the Civil Code. The conclusion of this research is that the revision of the Civil Code is a necessity in adapting to the challenges of the times. In terms of legal and grammatical substance, those who still adopt the old grammar are no longer appropriate to the current Indonesian language context. Likewise, articles that are no longer relevant need to be updated to ensure that the law continues to function effectively in modern society. The revision of the Civil Code is not just an adjustment, but is also an important step in modernizing the Indonesian legal system as a whole